FKP undergraduates won third place in A National-Level Design and Innovation Competition - Ismail, Khairuddin
Two undergraduates from the Faculty of Manufacturing Engineering (FKP), Universiti Malaysia Pahang (UMP) won third place in a national-level design and innovation competition held at Continental Hotel in Penang on July 4, 2013.